Model Layanan Peminatan berdasarkan Potensi Diri, Kondisi Sosiografis dan Perencanaan Karir Siswa SMA/SMK Kota BauBau - Wijaya, Rasman Sastra; Nurihsan, Juntika; Yusuf, Syamsu; Yustiana, Yusi Riksa; Edison, Edison; Manan, Manan; Tarno, Tarno; Gawise, Gawise; Wijaya, Fatma Pandu (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
The choice of specialization path or subject at school (SMA) is now based more on academic achievement alone, ignoring self-potential and sociographic conditions of students, making it possible for students to be confused about planning the right career choice. Putting aside the conditions of the area where he grows and develops, conditions include ethnic origin, social interactions, family status, kinship relations in the surrounding community, so that in his career he has difficulty planning the right career. The aim of this research is to produce a specialization service model based on personal potential, sociographic conditions and career planning for Baubau City High School students. The research uses a mixed method approach and is analyzed based on research and development. The research subjects were 127 students and 10 guidance and counseling teachers, taken using a purposive sampling technique plus 2 guidance and counseling experts spread across 13 high schools and vocational schools in Baubau. Data collection uses a specialization scale combined with sociographic conditions and career planning. The model was prepared hypothetically and limited trials from ten stages were reduced to 6 research stages to formulate an appropriate student specialization service model based on personal potential, learning achievement, and sociographic conditions and career planning. The model will have 9 components and effectively determine and provide recommendations for specialization based on personal potential, sociographic conditions, and the direction of students' future career planning more effectively and efficiently.